Effects of added fat, degradable intake protein, and ruminally-protected choline in diets of finishing steers - Flake, A.S.; Kuhl, Gerry L.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 216 yearling steers was used in two finishing experiments to evaluate interactions between levels of dietary fat, protein and ruminally protected choline. In Trial 1, steers received diets that combined levels of 0% or 5% added fat (choice white grease), 10.8% or 12.5% crude protein, and 0 or 5 grams per head daily of ruminally protected choline. Steers were fed in pens of five head each for 89 days. Adding fat decreased intake (P<.01), average daily gain (P<.1), and carcass weight (P<.07) and increased carcass yield grade (P<.06) but did not alter feed efficiency (P>.9). Increasing the protein level from 10.8 to 12.5% had no significant effects on live animal performance, but the high protein level resulted in a greater (P<.05) percentage of carcasses grading USDA Choice. Choline supplementation tended to increase average daily gain (P=.13) as well as the percentage of carcasses grading USDA Choice (P=.23). Choline also increased dressing percentage (P<.07); this effect was most pronounced when fat was not included in the diet, indicating an interaction between fat and choline (P<.1). In Trial 2, steers were fed a common finishing diet, which was top- dressed with ruminally protected choline at 2 to 9 grams per head daily or no added choline. Choline supplementation yielded linear improvements in rate of gain (P<.01), dry matter intake (P<.05), and carcass weight (P<.01). All measures of carcass fatness increased as the amount of choline increased. Adding ruminally protected choline to diets of finishing steers popusignificantly improved growth performance and carcass traits.
Keywords: Beef; Finishing cattle; Choline; Fat; Protein; Carcass